Implementasi Mudharabah Pada Pengembangan UMKM Wirausahaan Muda oleh BSI Maslahat Dalam Program Islamic Sociopreneur Development Program (ISDP) - Anisa Muzaqi; Dhiftania Luthfiya Azra; Fajar Hidayatullah; Nisa Azzahra; Zariah Sakinah Siregar (Madani: Jurnal Ilmiah Multidisiplin, 2023)
One of the main engines behind Indonesia's economic development is the growth of micro, small, and medium-sized businesses. However, there are still MSME actors who struggle with finding capital that occasionally is not sufficient to develop their businesses. This program may be one of the answers to their problems in doing so, as it offers mentors to help them in addition to financial assistance. This journal uses a qualitative research methodology. ISDP members are interviewed using qualitative research methodologies, and literature reviews examine reputable publications and materials. One of the sustainability initiatives developed by BSI and BSI Maslahat to serve as a venue for the distribution of community monies is the ISDP.Â